Land conflict resolution: Case study in Sarirejo Village - Aritonang, Juniaty D.; Hidayat; Zuska, Fikarwin (Future Science, 2021)
This study aims to describe the factors that cause land conflicts between the community and the Air Force in the Indonesian Air Force in Suwondo and the strategies that the community uses in demanding their land rights. The author chose a qualitative approach with the ethnographic method to understand more deeply what is behind an event that took the process, causes and conflict resolution. The results showed that the factor causing the conflict was the claim of each party to the land. Conflict resolution efforts are carried out by the community to obtain land rights through non-litigation advocacy processes and litigation advocacy. The results of these two strategies were able to encourage the government to restore community rights to their land even though it had to go through a long struggle. In July 2020 the government issued a policy to move the Sowondo Base to Langkat Regency.